2019
DOI: 10.1071/wr18119
|View full text |Cite
|
Sign up to set email alerts
|

Beach safety: can drones provide a platform for sighting sharks?

Abstract: ContextA series of unprovoked shark attacks on New South Wales (Australia) beaches between 2013 and 2015 triggered an investigation of new and emerging technologies for protecting bathers. Traditionally, bather protection has included several methods for shark capture, detection and/or deterrence but has often relied on environmentally damaging techniques. Heightened environmental awareness, including the important role of sharks in the marine ecosystem, demands new techniques for protection from shark attack.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 63 publications
(110 reference statements)
1
59
2
Order By: Relevance
“…Although most of the environmental variables we tested did not explain significant variation in the abundance of R. neglecta , wind had a significant negative effect on the number of individuals per transect. Wind can influence the detectability of marine wildlife during aerial surveys (Butcher et al ., ; Lubow & Ransom, ) and limiting surveys to days with favourable weather conditions has been recommended to avoid this issue (Kelaher et al ., ). The negative association between wind and cownose rays may also have been caused by R. neglecta moving offshore into deeper water during periods of strong winds.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the environmental variables we tested did not explain significant variation in the abundance of R. neglecta , wind had a significant negative effect on the number of individuals per transect. Wind can influence the detectability of marine wildlife during aerial surveys (Butcher et al ., ; Lubow & Ransom, ) and limiting surveys to days with favourable weather conditions has been recommended to avoid this issue (Kelaher et al ., ). The negative association between wind and cownose rays may also have been caused by R. neglecta moving offshore into deeper water during periods of strong winds.…”
Section: Discussionmentioning
confidence: 99%
“…Sea state parameters, such as visibility, wind speed and wind direction, had no effect on rates of animal detection. These findings, when considered alongside the significant body of literature supporting role these environmental factors on UAV survey success, seem somewhat counterintuitive [ 7 , 8 , 10 , 20 ]. However, these results reflect core ecological characteristics unique to the model system.…”
Section: Discussionmentioning
confidence: 92%
“…A large number of studies have reported this phenomenon, with similar levels of discrepancy, and have accredited this trend to many different factors [ 8 ]. These range from (i) the challenge for drone pilots to split their attention between flying and animal detection to (ii) technical difficulties involving telemetry screen resolution and glare [ 8 , 20 ]. However, unlike previous studies, all piloting for this project was carried out using first ‘person-view DJI goggles.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations